Innovative strategies for race walking learning through a traditional games approach to enhance learning motivation - Alvindo Dony Firmansyah; Astri Ayu Irawan; Asep Suherman (Universitas Sriwijaya, 2025)
Research Problems: Athletics is an engaging activity in physical education learning, but it is often less favored due to uninteresting material delivery. The implementation of traditional games in race walking lessons is expected to make the learning process more enjoyable and increase students’ interest and enthusiasm. Research Objectives: The purpose of this study was to determine the Effect of Variations in Traditional Games on Student Motivation in Race Walking Athletics Learning. Methods: This study used an experimental method with a One-Group Pretest-Posttest Design, where students' conditions were measured before and after treatment to determine the changes that occurred due to the application of traditional games. Results: The results of data analysis carried out with the help of SPSS 25 software showed a significant effect of the application of traditional games in race walking athletics learning. This is evidenced by the sig. (2-tailed) value of 0.000, which is smaller than the significance limit of 0.05. Conclusion: Thus, the implementation of traditional games in race walking athletics lessons has proven effective in enhancing students’ learning motivation, especially at the junior high school level. Further research is recommended with a broader scope and longer duration to examine the long-term effects on learning outcomes.